Rice Grain Classification using Fourier Transform Infrared Spectroscopy Technique and Laser Induced Breakdown Spectroscopy - Prihasty, Wilda (Diponegoro University Semarang Indonesia, 2025)
Rice is the main source of carbohydrates for Indonesian people and consumed to fulfill the nutritional needs of the body. The most commonly used method to find out nutrient content in rice grain is a chemical analysis based method that quite difficult and requires a considerable time. Therefore, spectroscopic-based measuring methods are the solution of these problems. A preliminary research is conducted to develop an accurate prediction methods of amylose, phenolic and flavonoids content, also elements contained in rice grain. Chemical analysis method used to determine of amylose, phenolic and flavonoid content then used as a validation. The predictive system is carried out using Partial Least Square (PLS) methods to determine amylose, phenolic and flavonoid content based on Fourier Transform Infrared (FTIR) spectrum. Meanwhile, Laser Induced Breakdown Spectroscopy (LIBS) used to figure out the elements contained in the rice. The Classification of rice grain using Principal Component Analysis (PCA) method based on FTIR and LIBS Spectrum. The results of this research, obtained a prediction system to determine levels of amylose, phenolic and flavonoids with the values coefficient of determination 0.95; 0.86; 0.95 and the RMSE value 1.4; 0.72; 0.44. Based on the spectrum of LIBS obtained from 13 types of rice grain, the elements contained in the rice grain are Mg, Fe, Na, K, Ca, C, H and O. The Classification of rice grain based on FTIR and LIBS spectrum obtained, namely High Quality; Premium and Medium.